Pengaruh Struktur Modal, Profitabilitas, Likuiditas dan Leverage Terhadap Nilai Perusahaan Studi pada Perusahaan Subsektor Farmasi yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023 - Harfia, Lilik Fasihatul; Pranjoto, R. Gatot Heru (Management Department of Economics and Business Of Trunojoyo Madura University, 2024)
This reìseìarch aims to deìteìrmineì and analyzeì theì influìeìnceì of Capital Struìctuìreì, Profitability, Liquìidity and Leìveìrageì on company valuìeì in pharmaceìuìtical suìb-seìctor companieìs listeìd on theì Indoneìsia Stock Eìxchangeì for theì 2019-2023 peìriod. Theì meìthod uìseìd was a puìrposiveì sampling meìthod and 7 companieìs weìreì obtaineìd. Theì teìchniquìeì uìseìd in this reìseìarch is muìltipleì lineìar reìgreìssion analysis and uìseìs quìantitativeì data. Baseìd on theì reìseìarch reìsuìlts, it shows that: (1) Capital struìctuìreì has a positiveì and significant eìffeìct on company valuìeì (2) Profitability has a positiveì and significant eìffeìct on company valuìeì (3) Liquìidity has a positiveì and significant eìffeìct on company valuìeì (4) Leìveìrageì has a neìgativeì and significant eìffeìct on valuìeì (5) Capital Struìctuìreì, Profitability, Liquìidity and Leìveìrageìsimuìltaneìouìsly influìeìnceì company valuìeì.